Biblical interpretation from the church fathers to the Reformation - Froehlich, Karlfried (Variorum collected studies series, 2010)
Christian interpretation of the Old Testament in the high Middle Ages -- Walafrid Strabo and the Glossa ordinaria : the making of a myth -- Makers and takers : the shaping of the biblical Glossa ordinaria -- The Glossa ordinaria and medieval preaching -- An extraordinary schievement : the Glossa ordinaria in print -- The printed gloss -- The fate of the Glossa ordinaria in the sixteenth century -- Martin Luther and the Glossa ordinaria -- Fallibility instead of infallibitity? : a brief history of the interpretation of Galatians 2:11-14 -- Saint Peter, papal primacy, and the exegetical tradition, 1150-1300 -- The chair of Peter : thoughts on an ancient Christian concept and its history -- Romans 8:1-11 : Pauline theology in medieval interpretation -- Paul and the late Middle Ages